Adult and child deprivation in Hong Kong. (13th August 2019) - Saunders, Peter; Tang, Vera Mun‐yu
Abstract: There is growing interest in the application of Townsend's deprivation approach to provide estimates of poverty that more directly reflect the living standards of those on low income. The consensual approach is applied here using data from the second wave (conducted in 2015–2016) of the Trends and Implications of Social Disadvantages in Hong Kong survey. The article draws on a related study that identifies separate lists of items deemed "necessary for all" by a majority of adults (aged 18 years or older) and children (aged 10–17 years). Those unable to obtain at least three of these items are identified as deprived, and the profile of household deprivation is examined in terms of the family types most affected, age groups, and numbers of children. Further analysis focuses on the disparity between children identified as living in households identified as deprived according to information provided by adults and children whose deprivation status reflects their own views. Finally, the overlaps between deprivation and four measures of poverty—two objective and income based and two subjective and perception based—are examined and discussed. The results indicate that deprivation and poverty are different but that, however it is measured, more needs to be done to address poverty in Hong Kong, including further improvements in the coverage and adequacy of health service provision and social security benefits.